Economic impacts of professional training in the informal sector the case of the labor force training program in Côte d'Ivoire - Verner, Dorte (Policy research working paper, 2005)
"The authors address the economic impact of the labor force training program (PAFPA) developed for the informal sector in Côte d'Ivoire. The data contain a subsample of the participants in the agricultural sector, tailoring sector, and the electronics sector, and a comparable control group of nonparticipants. The data have been analyzed using standard program evaluation tools, namely difference-in-difference estimators, in order to detect potential program impacts. The authors find positive economic impacts as a result of training received for some groups, namely women, the agricultural and electronics sectors, firms employing 1-3 individuals, and firms with 10 or more employees. "--World Bank web site